PENGARUH SLOW-STROKE BACK MASSAGE DENGAN MINYAK ESENSIAL YLANG-YLANG (Cananga odorata) TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI - Rahajeng Handayani (Coping: Community of Publishing in Nursing, 2014)
Hypertension is a major risk factor for cardiovascular disease is the leading cause of death in the elderly population in Indonesia. Objective of this research was to analyze the effect of slow-stroke back massage with ylang-ylang (Cananga odorata) essential oils to decrease blood pressure in elderly with hypertension in PSTW Jara Mara Pati Singaraja. Design of this research was a pre-experimental with one-group pretest-posttest approach. Sample consisted of 30 respondents with a total sampling technique. The results of the analysis with the Wilcoxon test showed that blood pressure significantly decrease in elderly with hypertension after treatment of slow-stroke back massage with ylang-ylang essential oils with value of ? = 0.000 is less than ? = 0.05. Based on the result, slow-stroke back massage with ylang-ylang essential oils can be used as an independent nursing intervention and safe therapy and effective in lowering blood pressure in elderly with hypertensive.